Multan’s Psychological School of Thought in Short-story Writing: (Case Study: Khalid Saeed’s Stories) - Misbah Khan; Dr Khawer Nawazish (Zaban-o-Adab, 2025)
Khalid Saeed is a notable short story writer associated with Multan’s psychological school of thought. The collection of his short stories “Sawal Ke Hath” (The Hands of Question) is a remarkable expression of social realism. He has particularly created characters who suffer from various psychological disorders. These characters are so deeply entangled in mental complexities that their social and domestic lives are severely affected. In his stories, Khalid Saeed has explored psychological terms and conditions such as the Oedipus complex, sadism, inferiority complex, selfishness, anger, frustration, and narcissism. His portrayal of such intricate mental states adds a profound psychological depth to his narratives. His fiction serves as a valuable tool for understanding the mental and emotional conditions of individuals within a societal context, reflecting the intersection of personal psyche and collective existence. This article presents a close study of Saeed’s short stories in the context of psychological criticism.